Challenges in inflected word processing for L2 speakers - The role of stem allomorphy - Salmela, Rosa; Lehtonen, Minna; Vainio, Seppo; Bertram, Raymond (CAMBRIDGE UNIV PRESS, 2025)
Morphological knowledge refers to the ability to recognize and use morphemes correctly in syntactic contexts and word formation. This is crucial for learning a morphologically rich language like Finnish, which features both agglutinative and fusional morphology. In Finnish, agglutination occurs in forms like aamu: aamu+lla ('morning: in the morning'), where a suffix is transparently added. Fusional features, as seen in ilta: illa+lla ('evening: in the evening'), involve allomorphic stem changes that reduce transparency. We investigated the challenges posed by stem allomorphy for word recognition in isolation and in context for L2 learners and L1 speakers of Finnish. In a lexical decision task, L2 speakers had longer response times and higher error rates for semitransparent inflections, while L1 speakers showed longer response times for both transparent and semitransparent inflection types. In sentence reading, L2 speakers exhibited longer fixation times for semitransparent forms, whereas L1 speakers showed no significant effects. The results suggest that the challenges in L2 inflectional processing are more related to fusional than agglutinative features of the Finnish language.